Severe Abdominal Pain Due To Gastrointestinal Obstruction in Patient With Lung Adenosquamous Metastases in Colon - Zata Dini; Pratiwi, Suryanti; Setyawan, Ungky; Budianto, Aries; Yudhanto, Hendy; Erawati, Dini (Malang Respiratory Journal, 2023)
Background: Lung cancer is the most common cause of cancer-related death globally. Moreover, metastatic cancer from the lungs frequently occurs and is commonly identified at the first diagnosis. The primary cancer must be identified in order to establish the most effective treatment. However, colonic metastases are rare with incidence of 0,1%. Aim: This report describes an unusual case of colonic metastases from lung adenocarcinoma. Methods: Patient (58-year-old male) was examined with Fiber Optic Bronchoscopy and core biopsy in the lungs, and the results were suspicious for squamous cells. The patient had severe abdominal pain and bloating for 1 week and had signs of gastrointestinal obstruction in his second visit. The result of urgent laparotomy was adenosquamous and the result of immunohistochemical examination was negative P40 and positive Napsin A in both lungs and colon. Results: The lung biopsy result indicated squamous cell and the ceccum showed adenosquamous. The immunohistochemical examination using P40 and Napsin A of both lung and ceccum specimens indicated that the lung was the primary source of metastases to the colon. Conclusion: The patient suffered from a squamous cell lung tumor and reported severe abdominal pain due to metastases to the colon with adenosquamous results.